KEPEMILIKAN INSTITUSIONAL, STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN NILAI PERUSAHAAN PADA SUB SEKTOR MAKANAN DAN MINUMAN - Ummi Kalsum; Randy Hidayat; Ingga Mawarni (Universitas Nusa Cendana, 2023)
The purpose of the study was to determine the effect of Institutional Ownership, Capital Structure, and Dividend Policy simultaneously and partially on Firm Value in the food and beverage sub-sector companies. The population in this study were all food and beverage sub-sector companies listed on the IDX in 2016-2020. The data sample was 45 observations selected through purposive sampling. The type of data in this study is secondary data. The analysis technique used is Multiple Linear Regression, F-test, and t-test. The results of the analysis show that Institutional Ownership, Capital Structure, and Dividend Policy simultaneously have a significant effect on Firm Value in food and beverage sub-sector companies, Institutional Ownership partially has no significant effect on Firm Value, Capital Structure partially has a significant effect on Firm Value, and Dividend Policy partially has a significant effect to Firm Value. Keywords: Institutional Ownership; Capital Structure; Dividend Policy; Firm Value